Polynomial semantics for modal logics. Issue 4 (2nd October 2019) - Agudelo-Agudelo, Juan C.; Echeverri-Valencia, Santiago
ABSTRACT: It is shown here that the modal logic K and any extension of it with a finite number of axioms can be characterised by a polynomial semantics. Moreover, some comments are made about the possibility of using algebraic computation to determine deducibility on these logics.